Strategi Pengembangan Desa Wisata dan Pariwisata Berkelanjutan melalui Program KKN untuk Mewujudkan Desa Sehat, Bersih, dan Edukasi - Dea Nurul Falah; Fathul amin; Dio riski saputra; Neli Septiawati Agustin; Ferti Della Triwinda; Silvia Kartisilawa; Rajudacosta Rajudacosta; Muhammad Nauful Zaky; Sri Choiriyati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of tourism villages is an effective strategy to improve community welfare and support the realization of sustainable development at the local level. This study aims to analyze strategies for developing a tourism village through the Community Service Program (Kuliah Kerja Nyata/KKN), with a particular focus on creating a healthy, clean, and educational village in Ambarawa, Pringsewu Regency. The research employed a descriptive qualitative approach, with data collected through field observations, in-depth interviews with village officials, community leaders, and local entrepreneurs, as well as documentation of program activities. The findings reveal that the implementation of the KKN program involved three main strategies. First, environmental hygiene and health education were carried out through socialization, mentoring, and community-based clean-up initiatives. Second, digital-based tourism promotion was developed using social media and online platforms, which increased destination visibility and enhanced tourist appeal. Third, local economic empowerment was strengthened by providing training and mentoring for Micro, Small, and Medium Enterprises (MSMEs), along with the introduction of non-cash transactions using QRIS to facilitate modern and efficient payments. These efforts successfully fostered community participation, raised environmental awareness, and stimulated innovative approaches to tourism promotion. Nevertheless, several challenges were identified, such as limited program duration, low levels of digital literacy among some residents, and the absence of comprehensive regulations governing tourism management. Recommendations include establishing a formal tourism management institution (Pokdarwis), enhancing capacity through digital literacy training, and fostering sustainable collaboration among government, academia, and the community to ensure that tourism village development can progress consistently, innovatively, and sustainably.